Conical zirconia telescoping into electroformed gold: A retrospective study of prostheses supported by teeth and/or implants. (19th February 2019) - Brandt, Silvia; Winter, Anna; Weigl, Paul; Brandt, Jan; Romanos, Georgios; Lauer, Hans‐Christoph
Abstract: Background: Telescopic prostheses are an evidence‐based treatment modality, and conical zirconia crowns and electro‐formed gold copings have been used for dentures supported by teeth and/or implants. Purpose: We aimed to evaluate the survival rates of zirconia‐based tooth/implant restorations. Materials and Methods: A total of 126 telescopic overdentures, all retained by conical zirconia crowns and electro‐formed gold copings, were retrospectively evaluated and failures analyzed for abutment configurations. Survival rates and modifying factors were evaluated by Kaplan‐Meier analysis, log‐rank testing, and Cox regression analysis. Results: We evaluated observation periods of up to 11.5 years (mean: 45.25 ± 25.11 months). Five‐year prosthesis survival was 96.9 ± 2.2% (95% CI: 92.6‐100). Six dentures had been lost, and these failures were significantly associated with specific abutment configurations. Conclusions: Within the limitations of this retrospective study, the concept of conical zirconia telescoping into electro‐formed gold provides a viable alternative to other telescopic designs used for removable dental prostheses. The concept is well suited especially for tooth/implant‐supported prosthetic rehabilitation.